Studies of natural killer cells in patients with paracoccidioidomycosis - Peraçoli, M. T.S. [UNESP]; Soares, A. M.V.C. [UNESP]; Mendes, R. P. [UNESP]; Marques, S. A. [UNESP]; Pereira, P. C.M. [UNESP]; Rezkallah-Iwasso, M. T. [UNESP] (Oxford University Press (OUP), 1991)
The number and activity of natural killer (NK) cells were studied in 34 untreated patients with paracoccidioidomycosis, 20 with the chronic form of the disease and 14 with the acute form. NK cells were detected with monoclonal antibody Leu-11c and the cytotoxic activity was measured using a single cell assay against K562 target cells. Both groups of patients had an increased number of circulating NK cells, their cytotoxic activity being significantly lower than in the healthy controls. These findings may be of importance in the immunological disturbances associated with paracoccidioidomycosis since NK cells exert important immune effector functions and may play a role in resistance against Paracoccidioides brasiliensis. © 1991 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.